Antioxidant and antibacterial activities of Ruta angustifolia extract - Muhammad Shuib, Nur Azfa; Mohamed Iqbal, Mohammad Anwar; Sulaiman, Fatimatul Akmal; Razak, Izzatie; Darnis, Deny Susanti (2015)

(untitled)
Objectives: To investigate antioxidant properties of R. angustifolia aqueous extract, to evaluate the correlation between polyphenolic contents of the R. angustifolia aqueous extract with the antioxidant activity and to determine the antibacterial activity of R. angustifolia methanolic extract against two Gram positive (Staphylococcus aureus ATCC 25923, Bacillus cereus ATCC 11778), two Gram negative (Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 8739). Methods: Aqueous maceration extraction was used for antioxidant activity and methanolic maceration extraction was used for antibacterial activity. The antioxidant properties and activity were evaluated by using total phenolic content (TPC), total flavonoid content (TFC), DPPH free radical scavenging activity and Beta-carotene bleaching method. Whereas, the antibacterial activity was examined using disc diffusion method against selected microorganism at concentration 1.0 mg/disc. Results: Results showed that the phenolic content of R. angustifolia extract was 18.89 g GAE/100g extract while the flavonoid content was 14.170 g QE/100g extract. R. angustifolia exhibited 2.04 mg/mL IC50 for DPPH free radical scavenging activity and 26.38% for average percentage inhibition for beta-carotene bleaching activity. While, the result for disc diffusion method showed no inhibition zone against all the strains of bacteria at 1.0 mg/disc concentration of the extract. Conclusion: Based on the result, it can be concluded that the R. angustifolia aqueous extract has the antioxidant properties and there is correlation between polyphenolic content of the extract with its antioxidant activity. However, R. angustifolia methanolic extract did not shown any antibacterial activity.